Manifestation of Love Theme in the Contemporary Mystical Poetry of Afghanistan Based on the Poetry of Majnon Shah Kabuli, Mastan Shah Kabuli and Heydari Wojodi - Tajuddin Arwinpoor; Mahsa Rone; Seyed Esmaiel Ghafelebashi (ادبیات عرفانی, 2022)
Research on the contemporary mystical literature of Afghanistan is a neglected field. Despite the current sufferings inflicting the country, the literature has more or less remained an active area. In this research, three mystical poets, Mastan Shah, Majnon Shah and Heydari Wojodi, who lived in the last one hundred years, have been briefly introduced and the concept of love, as the underlying theme of mystical literature, has been examined in their poetry. This study, adopting a descriptive-analytical method, sought to explore the following questions: What are the commonalities and possible differences between the poems of Majnon Shah and Mastan Shah, who followed Chishtiyyah order, and those of Heydari Wojodi, who followed the Naqshbandiyyah order; What is the place of love, as a condition for attaining perfection and knowing God, in the ontological orientation of Chishtiyyah and Naqshbandiyya orders? How have important issues like the contrast between love and reason and the relationship between material and real love reflected in the poems of these three poets? The results show that the poets, influenced by the unity of existence and the unity of intuition, considered love the origin of the universe and indefinable, and introduced it as the world of unity and the ultimate goal of the seeker; which frees him from reputation and shame. In the poems of Majnon Shah and Mastan Shah, whose mystical state is somewhat reminiscent of the state of Maulana's sonnets, also in the poems of Heydari Wojodi, which are influenced by his long engagement with Maulana's Masnavi, true love is considered as evolved form of material love and regarding the contrast between love and reason, all three poets have given priority to love over reason.